Understanding Groundwater Resource Vulnerability at Bryce Canyon National Park, Utah, Using Applied Geophysics at the Rubys Inn Thrust Fault - Trevor H. Schlossnagle; Kayla D. Smith; Tyler C. Gilkerson (Lithosphere)
Recent development near Bryce Canyon National Park, Utah, could affect local groundwater usage, availability, and dependent resources. The National Park Service and Utah Geological Survey conducted a geophysical study targeting the Rubys Inn thrust fault. This fault lies between commonly targeted aquifers in Emery Valley and groundwater flow systems of the Paunsaugunt Plateau, which support springs and dependent ecosystems. Fault zone geometry and internal structure are complex, resulting in a heterogeneous permeability distribution that affects groundwater flow. The influence of fault zones on groundwater flow parallel and perpendicular to their planes is difficult to predict. Geophysical imaging can yield important information about subsurface fault geometry. We utilized electrical resistivity tomography (ERT) surveys to investigate the influence of the Rubys Inn fault on groundwater occurrence and movement along the southeast boundary of Emery Valley. We collected ERT data along three transects orthogonal to the mapped fault strike in May and September 2022. Where available, we used water-level and lithologic data to constrain ERT inversion model interpretations. The inversion models illustrate the complexity and variability of the Rubys Inn fault within a short distance along strike. Where the fault is concealed, results indicate that the actual and mapped locations differ by 70–100 m along the transects. Groundwater is well constrained in the hanging wall, but poorly constrained in the footwall, and some seasonal variation is discernible. Variable stratigraphy and structure are apparent in all transects. This study enables strategic placement of test wells that will further establish the influence of the Rubys Inn fault on the occurrence and movement of groundwater in and adjacent to the fault zone. The study demonstrates that ERT is a cost-effective and noninvasive tool for detecting the precise surface location and delineating subsurface fault geometry in otherwise data-poor areas with sensitive ecological or archaeological resources.